Digitalisasi Keuangan UMKM Solusi Modern dan Efisien dengan Zahir Accounting - Ningtyas Rahmawati; Tino Kemal Fattah; Putriana Salman; Muhammad Syahid Pebriadi (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2025)
This research evaluates the implementation of Zahir Accounting as a digital financial management solution for UMKM Nazwa Sasirangan in Banjarmasin. The study aims to enhance operational efficiency and financial accuracy through the use of Zahir Accounting. The research employs a descriptive qualitative method, including data collection from financial records, observation, and structured interviews with key stakeholders. The analysis focuses on the financial performance of UMKM, examining aspects such as total assets, equity, revenue, cost of goods sold, operating expenses, and net income. Results indicate that Zahir Accounting significantly improves the accuracy of financial records and the transparency of financial reporting. The total assets of the UMKM reached Rp 93,163,833, with equity amounting to Rp 84,151,378. Despite recording a net loss of Rp 1,676,000 due to high cost of goods sold and operating expenses, the UMKM maintained a positive net cash flow from operating activities of Rp 14,129,000. The implementation of Zahir Accounting also reduced errors in transaction recording and facilitated more precise financial analysis. This research confirms previous findings that digital financial management tools can enhance the competitiveness and operational efficiency of UMKM. The study concludes that while the UMKM faces challenges in cost management, the adoption of Zahir Accounting provides significant benefits in terms of financial accuracy and strategic decision-making. Recommendations for future improvements include continuous training for staff, periodic evaluation of pricing strategies, and regular audits of operational costs. Overall, digitalization through Zahir Accounting is proven to be an effective modern solution for addressing financial management challenges in UMKM